Pengembangan Media Pembelajaran Interaktif Berbasis Genially Dalam Materi Pencatatan Persediaan Kelas XI Akuntansi Dan Keuangan Lembaga SMK Negeri 4 Surabaya - Listya Indriana; Rochmawati (Jurnal Pendidikan Akuntansi (JPAK), 2025)
The advancement of digital technology in education necessitates learning media that are not only visually engaging but also capable of fostering 21st-century skills such as critical thinking, creativity, collaboration, and communication. However, in practice, media used in schools have not fully adapted to technological developments and students’ learning needs, leading to low engagement and comprehension, particularly for complex topics such as inventory recording. This study aimed to develop Genially-based interactive learning media, assess its feasibility, and analyze students’ responses. The development process followed the ADDIE model, which includes Analysis, Design, Development, Implementation, and Evaluation. The analysis stage identified the need for attractive and interactive media. The resulting product contains inventory recording materials, practice questions, simulations, and quizzes. Instruments included validation sheets from subject matter, language, and media experts, as well as student response questionnaires. The trial was conducted with Grade XI Accounting students at SMK Negeri 4 Surabaya. Validation results indicated excellent feasibility, with scores of 93% from subject matter experts, 88% from language experts, 95% from media experts, and 99.48% from students. These findings suggest that the developed media is not only feasible for use but also effective in improving understanding of inventory recording. Genially-based interactive media facilitates teachers in delivering inventory recording material in an engaging and interactive way while fostering student independence and developing critical thinking, creativity, collaboration, and communication skills.